Use of extrapolation to forecast the working capital in the mechanical engineering companies - Cherep, A.; Shvets, Y. (Commission of Motorization and Energetics in Agriculture, 2014)
The purpose of the article is to study the method of extrapolation, highlighting the effectiveness of the financial activity of JSC «ZAZ» and for its future development. In the process of analyzing and exploring the scientific work of many scientists, effectiveness of using the extrapolation method for predicting performance was determined. As a result of research in the article analyzes the financial position of the enterprises of mechanical engineering in modern conditions, the efficiency of working capital in recent years determined. The feasibility of using the method of extrapolation in terms of instability of the market economy was investigated and proved. The forecast of working capital and total sales was made. It is offered to use in research the linear correlation coefficient of the pair, the method of least deviation, t – Student's criterion. Data obtained on the basis of the forecast enables businesses to improve their performance, to compete at a high level with other entities to establish a system of sales, to avoid crises in the future, increase profits and develop programs to reduce costs. Prospects for further research in this area will improve and develop an integrated system of economic methods on prediction performance of engineering enterprises based on current market position and variability of the environment.
Keywords: method of extrapolation; trend; coefficient of linear correlation; mean approximation error